Intunericul rosu inainte de apus . Red Darkness Before Dawn - Nicolae, Diana (Cineluci Production, 2003)
Duration: 01:07:00 This is a documentary dedicated to revealing and preserving the truth of what occurred in the prisons and labor camps of Communist Romania. Providing testimony of ex-political prisoners and historians alike, the film explores many of the torturous methods employed by the regime in Romania. By condemning the crimes of the past, the film serves as a sobering reminder of the methods of totalitarian regimes in the present, and if left undetected, in the future.